Androgenetic alopecia - just a cosmetic defect or a biomarker and risk factor for systemic diseases? - literature review - Suwała, Dawid; Pokrywka, Natalia; Polak, Marcelina; Koryszko, Klaudia; Hetnar, Paulina; Tomala, Magdalena; Kiper, Sebastian; Fortuna, Milena; Toczek, Sławomir; Jastrowicz-Chęć, Katarzyna (Journal of Education, Health and Sport, 2025)
Introduction: Androgenetic alopecia (AGA) is the most common cause of hair loss. It has traditionally been considered a cosmetic defect, but a growing body of evidence suggests that it may serve as a biomarker and risk factor for systemic diseases, suggesting its potential role in early disease detection and prevention. Purpose: The aim of this study is to review the available literature, analyze and summarize the current state of knowledge on the relationship between AGA and systemic diseases. Materials and research methods: The article is based on an analysis of PubMed and Google Scholar research. A literature review was conducted using the following keywords and medical subject headings: androgenetic alopecia; quality of life; cardiovascular disease; hair loss; metabolic syndrome; comorbidity. The analysis included clinical trials, systematic reviews, meta-analyses. Results: The analysis showed that patients with AGA were more likely to have cardiovascular disease, metabolic or endocrine disorders. Cases of increased risk of prostate and scalp cancers have also been described, as well as negative effects on mental health in people with AGA. These links underscore the need for an interdisciplinary approach to the patient and collaboration between the dermatologist and other specialists. Conclusion: AGA is not only an aesthetic problem, but can act as a biomarker for systemic diseases and be a signal for further diagnosis. Therefore, screening should be considered, as well as collaboration between dermatologists and other specialists. Future research should focus on the mechanisms linking AGA to other conditions, developing screening protocols, and analyzing the age of onset of AGA as a potential risk for systemic diseases.